ANALISIS KEBIJAKAN PAJAK DAERAH DALAM RANGKA MENINGKATKAN POTENSI PENDAPATAN ASLI DAERAH - Venden , Yuda Negara; Mulyadi, Edi; Hardian, Dafyar Eliadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This study aims to analyze regional tax policies to increase the potential for Regional Original Income (PAD) using a case study of the Tangerang City Regional Financial Management Agency (BPKD). The study employed a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman interactive model, encompassing data reduction, data presentation, and conclusion drawing. The theoretical basis of this research draws on William N. Dunn's (2003) theory of public policy evaluation, which encompasses effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy as criteria for policy analysis. Furthermore, the concept of public administration proposed by George J. Gordon and the public management theory of Shafritz & Russell are used to understand the role of public organizations in regional tax management. The definition of regional taxes refers to Mardiasmo (2011) and the provisions of Law Number 1 of 2022 concerning Central and Regional Financial Relations. The results of the study indicate that regional tax policies play a strategic role in strengthening regional fiscal capacity, particularly in the restaurant, hotel, and street lighting tax sectors. However, its implementation still faces obstacles such as low taxpayer compliance, limited human resources, and suboptimal technology utilization. Therefore, strengthening fiscal policy, modernizing tax administration, and synergy between stakeholders are needed to increase the effectiveness of local revenue (PAD) collection. This research is expected to provide theoretical contributions to the development of regional fiscal policy studies and practical recommendations for local governments in formulating more sustainable tax management strategies. Keywords: Regional Tax Policy, Locally-Owned Revenue, Taxpayer Compliance, Policy Effectiveness.